STRATEGI GURU AGAMA HINDU MENGATASI KETERBATASAN SUMBER PENDIDIKAN HINDU DI SMPN KECAMATAN GUNUNG BINTANG AWAI KABUPATEN BARITO SELATAN - kasih, Dona Mutiara; Mujiyono, Mujiyono; Astawa, I Nyoman Sidi (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2023)
This thesis examines the strategies of Hindu religious teachers in overcoming the limited resources of Hindu education at SMPN Gunung Bintang Awai District. The phenomenon that occurs is the limited number of Hindu religious teaching books, journals, pictures and symbols of the Hindu religion, the difficulty of the internet network which causes the learning of Hinduism to be less or not optimal. This research aims to examine and describe the strategies of Hindu religious teachers in overcoming the limited resources of Hindu education. This thesis uses a qualitative descriptive method with an emic approach. The results of the analysis studied using theory explain the strategies implemented by teachers at SMPN Gunung Bintang Awai District, namely participating in training, group work, accessing material from the internet, increasing teacher creativity, textbooks as learning resources and utilizing the learning environment. At SMPN Gunung Bintang Awai District, the use of educational resources is still not optimal because the availability of educational resources in these schools is still insufficient, teachers are less creative and innovative in overcoming limited learning resources such as conducting research and making learning books or modules.